"I didn't want to say something and them to go outside and tell everyone": The acceptability of a dissonance-based body image intervention among adolescent girls in the UK. (September 2021) - Jarman, Hannah K.; Treneman-Evans, Georgia; Halliwell, Emma
Highlights: Focus groups support acceptability of a dissonance intervention among UK girls. Peers played a critical role in participants' experience of the intervention. Initial concerns about disclosure were replaced with a sense of belonging over time. Participants transitioned from body dissatisfaction to positive body image. Insights and strategies which may improve participant engagement are discussed. Abstract: Cognitive dissonance-based interventions (CDIs) have been well established as effective programs for the prevention of eating disorders. However, limited research has qualitatively explored adolescent girls experience of such interventions. The present study examined the acceptability of a cognitive dissonance-based body image intervention among adolescent girls in UK secondary schools. Adolescent girls aged 14–18 years ( N = 99; M age = 14.87, SD = 0.97) who opted to participate in the intervention were invited to provide intervention feedback via open-ended questions and small focus groups. The findings suggest that the intervention was largely acceptable among adolescent girls. Peers played an important role. Despite initial concerns about sharing within the group, the groups provided a sense of belonging and participants no longer felt alone in their experience of body dissatisfaction. Participants discussed a transition from negative to positive body image following the intervention. Although acceptability was generally high, the data provides some interesting insights into potential considerations and modifications which may be advantageous in future CDIs. These include enhancing authenticity through reduced reliance on the script, inclusion of more personal content from the peer-leaders, and more interactive activities and physical movement.